Pembangunan Model Intervensi Kawalan Ketagihan Pornografi Berasaskan Pendekatan Psikospiritual Islam: Satu Analisis Keperluan : Development of Pornography Addiction Control Intervention Model Based on Islamic Psychospiritual Approach: A Needs Analysis - Mohd Suhaime, Ayu Nadhirah; Mansor, Nurul Husna; Rekan, Abd. Aziz; Mohammad Jodi, Khairul Hamimah; Zainal Abidin, Mohd Syukri (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
In today’s age of globalisation, pornography addiction is on the rise in society. This phenomenon not only occurs among adults but is also contagious among teenagers due to rapid technological development. Various efforts have been made to curb this problem. However, by 2022, the problem of pornography addiction has not abated, as traffic statistics of visitors to pornography websites show increasing access by users. Pornography is forbidden and sinful in Islam because it exposes human private parts to people who do not have the right to see them and, at the same time, encourages human desires towards acts that violate Islamic laws. Islam also sees pornography as a form of disease that harms the human soul and spirit, leading people to commit sexual crimes such as extramarital sex, cybersex, rape, obscenity, and child abandonment. Therefore, this article is presented as a preliminary survey to identify the need for the development of a pornography addiction control intervention model based on the Islamic psychospiritual approach. This article uses a qualitative approach by analyzing the documents of past studies related to Islamic psychospiritual treatment to deal with this addiction issue. The study's findings revealed the need for the development of a pornography addiction control intervention model based on the Islamic psychospiritual approach to dealing with the community's physical, mental, spiritual, and moral health problems.